The role of DNA sensors in recognition of pathogen-associated molecular patterns of infectious pathogens and the development of inflammation. Part 2. HIN-200 proteins Family - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2014)
The survey characterized HIN-200 proteins molecular family and their role in the development of infection.